Human Resource Quality, Leadership, And Working Motivation as Predictors of Sales-Related Performance in North Bekasi Public Offices - Supardi Supardi; Shalahuddin Shalahuddin; Muhammad Takrim; Lala Wiladiyah; Hari Sapto Yudiarso (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the roles of human resource quality, leadership, and work motivation in improving sales-related performance in public offices located in North Bekasi, Indonesia. In this article, sales-related performance is operationalized as target achievement, outcome growth, service effectiveness, stakeholder satisfaction, and revenue realization rather than purely commercial sales. The study used a quantitative explanatory design based on 150 employee-level observations from ten anonymous public offices. Four latent variables were measured with twenty Likert-scale indicators and analyzed using covariance-based structural equation modeling reported in the AMOS 24 convention. The measurement model demonstrated acceptable convergent reliability, with standardized loadings ranging from 0.652 to 0.820 and composite reliability values ranging from 0.820 to 0.852. The structural model achieved very good model fit (χ² = 150.558; df = 164; p = 0.766; CMIN/DF = 0.918; GFI = 0.986; AGFI = 0.982; CFI = 1.000; TLI = 1.013; RMSEA = 0.000; SRMR = 0.048). The standardized path estimates show that leadership has the strongest positive effect on sales-related performance (β = 0.465; CR = 6.134; p < 0.001), followed by work motivation (β = 0.338; CR = 4.548; p < 0.001) and human resource quality (β = 0.270; CR = 4.044; p < 0.001). The model explains approximately 65.4% of the variance in sales-related performance. These findings indicate that leadership capability, employee motivation, and HR quality should be managed as an integrated performance system in public offices with target-based services or revenue realization responsibilities.